Sistem Pendukung Keputusan untuk Penilaian Kinerja Karyawan Biller di Kantor ULP Kuala Menggunakan Metode TOPSIS - Sri Defriani Br Sembiring; Suci Ramadani; Anton Sihombing (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Employee performance appraisal is a crucial aspect of human resource management and development, as the evaluation results serve as the basis for managerial decision-making, including promotions, incentives, and career development. However, unstructured assessment sistems often hinder the objectivity, transparency, and accuracy of performance evaluations. This study aims to design and develop a web-based Decision Support Sistem (DSS) to assess the performance of Biller employees at the ULP PLN Kuala office by applying the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. TOPSIS was selected because it effectively addresses multi-criteria decision-making problems by comparing each alternative to both positive and negative ideal solutions. The evaluation criteria include invoice achievement, account return balance, and PAL balance. The sistem was developed using PHP as the programming language and MySQL as the database, ensuring integration and accessibility. The test results indicate that the sistem is capable of providing employee rankings in an objective and measurable manner. Based on the calculation, Tri Widodo achieved the highest score (0.8027), demonstrating the best performance among the evaluated employees. The implementation of this TOPSIS-based DSS makes the performance appraisal process more sistematic, efficient, transparent, and accurate, thereby contributing to the improvement of human resource management quality within the organization.